PENGARUH TIME BUDGET PRESSURE, PENGALAMAN AUDITOR DAN AUDIT TENURE TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI WILAYAH KOTA MEDAN - Herlina Herlina; Christiana Gultom; Talenta Marpaung (Yayasan Akrab Pekanbaru, 2019)
This study aims to determine the effect of Time Budget Pressure, auditor experience and Audit Tenure both partially and simultaneosly to audit quality at public accounting firm of region medan city. The test use in the study is the survey method, the type of data studied is quantitative data, the populations of study are auditors who worked at public accounting firm of medan by confinient sampling method with the number of respondents as many as 80 and the result showed that partially and simultaneous the variable of Time Budget Pressure, auditor’s experience and Audit Tenure has significant effect on audit quality. The researcher suggests that for future research to be able to improve this research such as adding more variables and expanding the population.